2016
DOI: 10.1016/j.pharmthera.2016.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional culture systems in cancer research: Focus on tumor spheroid model

Abstract: Cancer cells propagated in three-dimensional (3D) culture systems exhibit physiologically relevant cell-cell and cell-matrix interactions, gene expression and signaling pathway profiles, heterogeneity and structural complexity that reflect in vivo tumors. In recent years, development of various 3D models have improved the study of host-tumor interaction and use of high-throughput screening platforms for anti-cancer drug discovery and development. This review attempts to summarize the various 3D culture systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
667
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 700 publications
(716 citation statements)
references
References 161 publications
7
667
0
9
Order By: Relevance
“…A main precondition for high-throughput screening is the reproducibility of uniform spheroids as size and heterogeneity may influence the validity of end-point assays (45). We showed that spheroids grow in a linear pattern with higher proliferation rates in ULA plates resulting in significant increased spheroid sizes compared to HD.…”
Section: Anticancer Researchmentioning
confidence: 84%
See 4 more Smart Citations
“…A main precondition for high-throughput screening is the reproducibility of uniform spheroids as size and heterogeneity may influence the validity of end-point assays (45). We showed that spheroids grow in a linear pattern with higher proliferation rates in ULA plates resulting in significant increased spheroid sizes compared to HD.…”
Section: Anticancer Researchmentioning
confidence: 84%
“…Typical spheroid architecture, consisting of a an inner layer of quiescent cells and an outer layer of proliferating cells, respectively, was detected in MCTS lager than 500 μm in diameter, an indication of nutrition, oxygen and, thus, proliferation gradients responsible for cell heterogeneity (29,32,47). These limited diffusion gradients of oxygen, nutrients, metabolic waste products and soluble factors, such as cytokines and growth factors, were shown to be similar to micro-metastases and avascular tumors measuring 0.5-1.0 mm 3 (37,45,48).…”
Section: Anticancer Researchmentioning
confidence: 87%
See 3 more Smart Citations